MENINGKATKAN KEMAMPUAN REPRESENTASI MATEMATIS DAN SELF CONCEPT MELALUI ACCELERATED LEARNING CYCLE MTS NEGERI 3 BANYUMAS - Leisita Sherly Cendana; Anggun Badu Kusuma (Jurnal Karya Pendidikan Matematika, 2019)
The study aimed to improve students’ mathematical representation and self-concept skills through Accelerated Learning Cycles (ALC). This study is Classroom Action Research (CAR) carried out in 3 cycles. The stages in each cycle were planning, implementation, observation, evaluation, and reflection. The research subjects were students of grade VII B of MTs Negeri 3 Banyumas in 2018/2019 academic year. The instrument used was a descriptive test to measure students’ mathematical representation skills provided at the end of each cycle and to determine students’ self-concepts through a questionnaire. Based on the findings, mathematical representation skills obtained an average value of 56,81 in the first cycle, 75,38 in the second cycle, and 80,86 in the third cycle. The results of the average value of students’ self-concept questionnaire for cycle I was equal to 64,85, 67,66 in the second cycle, and 70,65 in the third cycle. It can be drawn that the Accelerated Learning Cycle (ALC) could improve students’ mathematical representation skills and self-concept.